The 12 amazing secrets of millionaire inventors : - Reese, Harvey (John Wiley & Sons, 2007)
In The 12 Amazing Secrets of Millionaire Inventors, Harvey Reese, the creator of inflatable furniture, pet antlers for Christmas, and more than 100 other licensed inventions, shows you how to make your creativity pay off big-time. Reese explains all your options—including licensing your idea to another firm, selling it outright for a one-time fee, producing and marketing it yourself, or franchising it to other entrepreneurs. Each option can make you money, but how do you know which to choose? Reese provides a step-by-step process that helps you figure out how to make the most money based on what you want to achieve and the resources you have at hand. Plus, he provides a truckload of handy checklists, contracts, legal forms, patent office information, and other resources every new inventor needs. Don't wait—get started now with in-depth advice on: The most common mistakes new inventors make. Protecting your idea through patents, trademarks, and copyrights. Finding investors to bankroll your idea and your business